Urticarial rash as the initial presentation of COVID‐19 infection: A case report - Usamah Al‐Anbagi; Shybin Usman; Abdulqadir J. Nashwan (Clinical Case Reports, 2022)
Abstract During the COVID‐19 pandemic, various skin manifestations have been described. These include an urticarial rash, morbilliform rash, maculopapular rash, vascular lesions, and varicella‐like eruptions. A 30‐year‐old woman presented with a mild cough, then hives and pruritic rash for 3 days, followed by fever, dyspepsia, and throat pain for one day.